1995
DOI: 10.1002/bscb.19951040404
|View full text |Cite
|
Sign up to set email alerts
|

HDS AND HDN ACTIVITY AND CHARACTERIZATION OF NiMo ‐USY ZEOLITE CATALYSTS

Abstract: INTRODUCTIONHydrotreating reactions such as HDS, HDN and HC are usually conducted on mixed transition metal sulfides (Ni-Mo or NI-W) supported on carriers which are more or less acidic depending on the function to be promoted (1). As pointed out by Pratt et al.(2) the carrier has a marked effect on the specific activity of the sulfide catalysts. However, alumina, which is the most used carrier for this type of catalysts, offers only a moderate cracking activity and requires severe hydrotreating of the feedstoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The Mo 3d 5/2 peak of all spent catalysts exhibited binding energy at 229.3 eV because of MoS 2 species . In this study, all catalysts showed complete sulfidation of molybdenum species.…”
Section: Resultsmentioning
confidence: 49%
“…The Mo 3d 5/2 peak of all spent catalysts exhibited binding energy at 229.3 eV because of MoS 2 species . In this study, all catalysts showed complete sulfidation of molybdenum species.…”
Section: Resultsmentioning
confidence: 49%
“…However, high acidity of zeolites will result in deep cracking or secondary reactions in the catalytic processes. For the deep desulfurization reactions, for example, it should be required a suitable degree of acidic functionality in order to improve the ring-opening of heterocyclic aromatic components, which is prior to the conversions of organic heteroatomic compounds to inorganic sulfur and nitrogen species . It has been reported that the incorporation of acidic zeolites in catalysts could promote the hydroisomerization and dealkylation activities of a catalyst. , On the other hand, these acidic materials tended to possess either only micropores (less than 2 nm) or only mesopores (2−50 nm), in most cases only micropores .…”
Section: Introductionmentioning
confidence: 99%